Tackling Crime and Fear of Crime Whilst Waiting at Britain's Railway Stations - Cozens, Paul; Neale, R.; Whitaker, J.; Hillier, D. (2004)
Crime on the railways in Britain is an increasing concern for train operating companies,the British Transport Police (BTP), passengers, and local residents. Significantly,rail users consistently perceive their risks from crime to be considerably higher thanofficial crime statistics indicate, having a negative affect on levels of patronage. Thisarticle presents an exploratory study of passengers’ fear of crime while waiting atrailway stations using Quick Time Virtual Reality (QTVR) walkthrough scenes. QTVRarguably represents an innovative, dynamic, and interactive environmental stimulusfor gaining insights into passengers’ fear of crime. Visibility at stations was identifiedas a crucial factor in determining levels of fear of crime. The design of the stationshelter is analyzed as an example of how crime prevention through environmentaldesign (CPTED) is being implemented on railway stations by Valley Lines (Wales and Borders Trains) on its network in South Wales (UK).